Evaluating the clinical efficacy of maxillary labial frenectomy procedure using diode laser (980 nm) and conventional scalpel: An observational study - Kiran Vincent; Sachin Aslam; Roshni Abida; Tom Thomas; Mathew Pynummoottil Cherian; Sooraj Soman (Wolters Kluwer Medknow Publications, 2023)
Aim: This is an era of minimally invasive and least traumatic surgical interventions being focused on. The traditional scalpel frenectomy technique offers an increase in post-operative sequelae. To unravel this scenario a comparative evaluation is carried out to find out the clinical outcomes and quality of life after maxillary labial frenectomy using a conventional scalpel and diode laser frenectomy of 980 nm. Materials and Methods: Thirty-six subjects age ranging between 18 and 45 years reported to the Department of Oral and Maxillofacial Surgery, MES Dental College, Perinthalmanna with an aberrant frenal attachment of maxillary labial frenum were randomly assigned into two groups. Group A underwent the conventional scalpel technique and group B for the diode laser-assisted (980 nm) frenectomy technique. The post-operative parameters of ooze from the surgical site, pain, wound healing, and discomfort or acceptance of the procedure were assessed on day 1, day 7, and day 14, respectively. Results: The diode laser group exhibited statistically significant clinical and healing outcomes. Less pain, minimal or absent ooze, increased healing, and better acceptance of the procedure with diode laser at 1, 7, and 14 days recall visit. Conclusion: Surgical interventions involving needle puncture and the associated post-operative sequelae are the most dreaded experiences that make patients indifferent toward surgical treatments. Thus in terms of better clinical outcomes and improved quality of life diode laser frenectomy is an excellent alternative wherein a needleless anesthetic success followed by minimal surgical intervention and less post-operative sequelae with fast recovery is possible.